2015
DOI: 10.1002/dev.21307
|View full text |Cite
|
Sign up to set email alerts
|

Episodic memory and future thinking during early childhood: Linking the past and future

Abstract: Despite extensive examination of episodic memory and future thinking development, little is known about the concurrent emergence of these capacities during early childhood. In Experiment 1, 3-year-olds participated in an episodic memory hiding task [“what, when, where” (WWW) components] with an episodic future thinking component. In Experiment 2, a group of 4-year-olds (including children from Experiment 1) participated in the same task (different objects and locations), providing the first longitudinal invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 63 publications
5
8
0
Order By: Relevance
“…Taken together, these data add to a growing body of work showing that episodic memory emerges much earlier in development than was previously envisaged (Cuevas, Rajan, Morasch, & Bell, 2015;Hayne & Imuta, 2011). Consistent with her prior research, young children in the present study exhibited excellent nonverbal memory when they were tested after a 24 hr or a 1-year delay.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Taken together, these data add to a growing body of work showing that episodic memory emerges much earlier in development than was previously envisaged (Cuevas, Rajan, Morasch, & Bell, 2015;Hayne & Imuta, 2011). Consistent with her prior research, young children in the present study exhibited excellent nonverbal memory when they were tested after a 24 hr or a 1-year delay.…”
Section: Discussionsupporting
confidence: 90%
“…Irrespective of the delay, children described their prior experience from their own, first-person perspective, demonstrating the kind of autonoetic consciousness that is considered to be the hallmark of episodic memory. Taken together, these data add to a growing body of work showing that episodic memory emerges much earlier in development than was previously envisaged (Cuevas, Rajan, Morasch, & Bell, 2015;Hayne & Imuta, 2011).…”
Section: Discussionsupporting
confidence: 66%
“…Since then, several studies have used different variants of the Spoon test to assess future thinking in children (e.g., Atance & Sommerville, 2014; Cuevas, Rajan, Morasch, & Bell, 2015; Dickerson, Ainge, & Seed, 2018; Russell, Alexis, & Clayton, 2010). Overall, all these studies typically show an age‐related improvement in the Spoon test between ages 3–5.…”
Section: Main Nonverbal Experimental Approaches To the Study Of Mentamentioning
confidence: 99%
“…Suddendorf et al (2011) adapted Tulving's idea by presenting children with a problem (e.g., locked box with no key) in room A and a set of items (including a key) in room B. Their study showed that 4 but not 3 year olds choose the correct item to take back to room A (for similar results see: Atance and Meltzoff, 2005;Russell et al, 2010;Redshaw and Suddendorf, 2013;Scarf et al, 2013;Atance and Sommerville, 2014;Atance et al, 2015;Cuevas et al, 2015;Dickerson et al, 2018). Overall, these studies typically show an age-related improvement in future thinking between ages 3 to 5.…”
Section: Introductionmentioning
confidence: 96%